Construction and Testing of A Teacher Productivity Model for Special Schools Using POP-SDM and SEM-PLS - Iswari, Fitria; Setyaningsih , Sri; Suhendra (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Inclusive education is an effort to fulfill the right to education for all children, including children with special needs. However, its implementation still faces various challenges, particularly in the learning process at Special Schools (SLB). Therefore, increasing teacher productivity is an important factor in improving the quality of special education services. This study aims to analyze the influence of growth mindset, transformational leadership, cooperation, work motivation, and creativity on the work productivity of SLB teachers through the POP-SDM approach with Structural Equation Modeling–Partial Least Square (SEM-PLS) analysis. This study uses a quantitative method with multi-stage random sampling techniques on 140 SLB teachers with civil servant status in the Province of Jakarta. Data collection was conducted through a survey using a questionnaire instrument for each research variable. The research model consisted of three exogenous variables, namely growth mindset, transformational leadership, and cooperation, two intervening variables, namely work motivation and creativity, and one endogenous variable, namely teacher productivity. The results showed that the model met the SEM-PLS model feasibility criteria, had good predictive relevance, and showed strong predictive power based on PLS Predict analysis. The coefficient of determination value indicated that work motivation contributed significantly to teacher productivity